Indeks Saham Syariah Indonesia Saat Pandemi Covid’19 - Nurokhmawati -; Pardi Pardi (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to analyze the effect of Inflation, Rupiah/Dollar Exchange Rate, and Bank Indonesia Sharia Certificates on the Indonesian Sharia Stock Index for the period March 2017 to October 2020. The secondary time series data used are 44 data periods. The method of analysis with multiple linear regression and classical assumption test and hypothesis testing. The results show that the rupiah exchange rate has a significant effect on the Sharia Stock Index in Indonesia. Unlike the Indonesian Sharia Stock Index, it is not significantly affected by inflation and Bank Indonesia Sharia Certificates. Keyword : Index, Sharia Stock, Covid’19 Pandemic